Economics meets psychology: Experimental and self-reported measures of individual competitiveness - Werner Bönte; Sandro Lombardo; Diemo Urbig (University of Wuppertal, Schumpeter School of Business and Economics, 2016)
Economists and psychologists follow different approaches to measure individual competitiveness. While psychologists typically use self-reported psychometric scales, economists tend to use incentivized behavioral experiments, where subjects confronted with a specific task self-select into a competitive versus a piece-rate payment scheme. So far, both measurement approaches have remained largely isolated from one another. We discuss how these approaches are linked and based on a classroom experiment with 186 students we empirically examine the relationship between a behavioral competitiveness measure and a self-reported competitiveness scale. We find a stable positive relationship between these measures suggesting that both measures are indicators of the same underlying latent variable, which might be interpreted as a general preference to enter competitive situations. Moreover, our results suggest that the self-reported scale partly rests on motives related to personal development, whereas the behavioral measure does not reflect competitiveness motivated by personal development. Our study demonstrates how comparative studies such as ours can open up new avenues for the further development of both behavioral experiments andpsychometric scales that aim at measuring individual competitiveness.
urn:nbn:de:hbz:468-20161125-121944-6
Keywords: C91; D03; M52; 330; Competition; Experiment; Tournament scheme; Personal Development Motive